(untitled) (Bangladesh Medical Journal, 2019)
ESWL is one of the treatment modalities for kidney stones smaller than 2 cm. However, not all ESWL treatments are successful. The success rate has been reported to be between 50% to 87%, depending on various factors. This study was conducted to evaluate factors affecting the success rate of renal stone treatment by extracorporeal shock wave lithotripsy (ESWL). The study was carried out for a period of one year where total 96 patients with single or multiple radio-opaque renal stones treated with ESWL monotherapy using Stortz Modulith SLX-F2 lithotriptor were included. The results of treatment were evaluated after 3 months of follow-up. Treatment success was defined as complete clearance of the stones or presence of clinically insignificant residual fragments (<4mm). The results of treatment were correlated with the patient characteristics (age, sex, body mass index) and stone features (size, site, number and radio density). At 3-months follow-up, the overall success rate was 76%. Among them, repeated ESWL sessions were required in 19 patients (53.9%). Post-ESWL complications were recorded in 8 patients (12.5%). Four factors had statistically significant impact on the success rate, namely stone site, size (the largest diameter of the stone), stone number, BMI (body mass index) of the patient. The success rate is highest for stones located in the upper calyx (26/26; 100%) and lowest for those located in lower calyx (15/20; 75%) (p=0.019). Stone with a largest diameter of <15mm are associated with a success rate of 93.6% (59/63), compared to 75.82% (25/33) for those with a diameter of >15mm (p=0.01). The success rate is also higher for single stone (76/84; 90.5%) than multiple stones (8/12; 66.7%) (p=0.02). Patients with lower BMI (<24) have a better success than higher BMI (>25) (p=0.001).Other factor including age, sex and stone radio density compared to ipsilateral 12th rib have no significant impact on the success rate. The success rate for ESWL for the treatment of renal stones can be predicted by stone size, location, number, and patient BMI. Bangladesh Med J. 2017 May; 46 (2): 1-6